2013
DOI: 10.3109/01612840.2013.857200
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric-Mental Health Nurses and the Sex Trafficking Pandemic

Abstract: Nurses are in a unique position to treat survivors of human trafficking and are most likely to encounter patients who have been involved in the sex trade. In particular, psychiatric-mental health nurses can be effective because they are educated to think of clients holistically and can provide both short-term medical intervention and long-term psychotherapy. Additionally, they can recognize and refer these individuals for medical treatment. The purpose of this article is to present an overview of sex trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Affirming previous literature (George, McNaughton, & Tsourtos, 2016), the project found that, with a few exceptions, trafficked persons remained invisible when interacting within the health system. Similar to previous international studies (Alpert et al, 2014;De Chesnay, 2013;Dovydaitis, 2010), this invisibility was aided by professionals who were unaware of the multiple and interrelated symptoms endured by trafficked persons and who were unskilled in the techniques that could be employed to recognise them. In the absence of adequately equipped workers, misidentification and limited preparedness to respond to the needs of trafficked persons will remain a major barrier to effective service provision, as will the professional's ability to confidently identify, treat and refer trafficked persons.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Affirming previous literature (George, McNaughton, & Tsourtos, 2016), the project found that, with a few exceptions, trafficked persons remained invisible when interacting within the health system. Similar to previous international studies (Alpert et al, 2014;De Chesnay, 2013;Dovydaitis, 2010), this invisibility was aided by professionals who were unaware of the multiple and interrelated symptoms endured by trafficked persons and who were unskilled in the techniques that could be employed to recognise them. In the absence of adequately equipped workers, misidentification and limited preparedness to respond to the needs of trafficked persons will remain a major barrier to effective service provision, as will the professional's ability to confidently identify, treat and refer trafficked persons.…”
Section: Discussionmentioning
confidence: 79%
“…The cumulative harm of each stage of trafficking (recruitment, travel-transit, exploitation, detention and integration or reintegration stages of trafficking) results in adverse and multiple inter-related physical, reproductive, developmental, behavioural and psychological health impacts (Zimmerman, Kiss & Hossain, 2011). These interact with the personal, socialenvironmental, and contextual systemic factors specific to the trafficked person (Alpert, Ahn, Albright, Purcell, Burke, & Macias-Konstantopoulos, 2014;Banović & Bjelajac, 2012;De Chesnay, 2013;Dovydaitis, 2010;Gibbons & Stoklosa, 2016;Schwarz, Unruh,Cronin, Evans-Simpson, Britton, & Ramaswamy, 2016). Regardless of the reason for being trafficked, an individual's development and life trajectory is negatively disrupted.…”
Section: The Health Needs Of Trafficked Personsmentioning
confidence: 99%
“…Effective social services, however, inherently nurture agency after trust is established (e.g., de Chesnay, 2013;Johnson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Underage clients who are victimized may present with sexually transmitted diseases or infections (STD/STI). Often victims of human trafficking appear fearful, anxious, or uncooperative, or they may present with a flat affect and be emotionless (de Chesnay, 2013;McNulty, 2013;Peters, 2013;Sabella, 2011;Trout, 2011). …”
Section: Signs and Indicators Of Human Traffickingmentioning
confidence: 99%
“…It has been noted that nurses are positioned to identify and rescue victims of human and sex trafficking. Nurses are clinically placed in psychiatric centers, urgent care centers, emergency departments, and physician offices where victims of human trafficking may be taken for treatment of illness and injury (de Chesnay, 2013, Hom & Woods, 2013, Newby & McGuinness, 2012, Peters, 2013. Hom and Woods (2013) noted that trauma sensitive services should include better screening methods among first responders and health care professionals.…”
Section: Human Trafficking Content In Nursing Curriculummentioning
confidence: 99%